PENANGANAN KELUHAN TAMU OLEH PRAMUSAJI DI RESTORAN THE VIEW HOTEL ROYAL ASNOF PEKANBARU - Putri, Septi Riana; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The rapid development of the world of tourism is not only marked by the number of tourist attractions but also can be marked by the number of new hotels built in various cities. A good hotel is judged by the good or not service provided. Good and bad service determines whether or not many complaints are given by guest. The complaints is given by guests must be resolved by the hotel staff, especially the waiter because dealing directly with guests when complaints occur in the restaurant. The handling complaints must has stages in solution. And everything must be resolved quickly and precisely. This study aims to determine how to handle complaints that occur in The View Hotel Royal Asnof Pekanbaru restaurant. This research uses descriptive qualitative method to analyze problems based on data collection techniques of interviews, observations, and documentation which can then be drawn conclusions. The subject of this research was obtained from interviews with key informants like HRD, F&B Service Manager, Supervisor, and Waiters. And the results of the research carried out like how the hotel's staff especially the waiter when their trying to handle the complaints. And the handling complaints is focused on complaints that occur because of the service and atitude the waiters when their are face up to the guest. Although this does not rule out the possibility of a complaint in the future because it cannot be avoided, therefore special attention is needed for handling the complaint. So the restaurant The View Hotel Royal Asnof Pekanbaru can not be said regardless of the name of the complaint. Keywords: The Handling of Guest Complaints